Epidemiological and microbiological aspects of acute bacterial diarrhea in children from Salvador, Bahia, Brazil - Diniz-Santos,Daniel R. (2005)
In the few cases of acute childhood diarrhea that require antimicrobial therapy, the correct choice of the drug depends on detailed previous knowledge of local strains. In order to establish such parameters in our city, we reviewed the results of all 260 positive stool cultures of children between 0 and 15 years of age during two years at a pediatric tertiary care facility in Salvador, Brazil. Bacterial strains had been presumptively identified by culturing in selective media and by biochemical testing, and their antimicrobial susceptibility patterns were automatically detected by the MicroScan Walkaway System. Data about patients' sex and age, monthly distribution of the cases, pathogens isolated and their antimicrobial resistance patterns were recorded. Males corresponded to 55.4% of our sample, and most of our patients (42.7%) were between one and four years of age. Shigella was the commonest pathogen, being found in 141 (54.3%) cultures, while Salmonella was found in 100 (38.4%) cultures and Enteropathogenic E. coli in 19 (7.3%). Salmonella was the main causal agent of diarrhea in children younger than five years old, whereas Shigella was the most frequent pathogen isolated from the stools of children between five and 15 years old. The peaks of incidence correspond to the periods of school vacations. Shigella specimens presented a very high resistance rate to trimethoprim-sulfamethoxazole (90.1%) and to ampicillin (22.0%), while Salmonella presented very low resistance rates to all drugs tested. These data are useful for practitioners and they reinforce the need for continuous microbiological surveillance.